The Factors that have led to increased HIV/AIDS Prevalence among Adolescents aged 13-21 Years in Hoima Regional Referral Hospital, Hoima District. A Cross-Sectional Study. - Caleb Kusilika (Student's Journal of Health Research, 2022)
Background: The study's broad objective was to determine the factors influencing the increasing prevalence of HIV/ AIDS among adolescents to suggest relevant and appropriate interventions that may be applied in the future in order to decrease the prevalence and combat HIV/ AIDS. Methodology: A cross-sectional study was carried out at Hoima Regional Referral Hospital to determine the factors which have influenced HIV/AIDS prevalence among adolescents from 12th March 2013 to 18th March 2013. Data were collected from adolescents who attended OPD services and it involved interviewing the adolescents using a questionnaire by the researcher on the demographics, HIV-related knowledge, awareness, and attitudes on preventive measures and social factors that influence the increase in HIV prevalence. The data was analyzed manually using a scientific calculator and was compiled in form of tables, pie charts, and bar graphs Results: Unplanned sex (35%), Beautiful partners (22%), the influence of partners (4%), presence of AVRs(10%), and Fear to buy condoms(29%), were the factor that has led to the increased HIV/AIDS amongst adolescents.  Conclusion: The involvement of other sectors of a community like local councils, learning institutions, churches, civil society organizations, and NGOs will do a long way in promoting effective knowledge to the adolescents about HIV preventive measures. Recommendations: The government through the ministry of health should continue to sensitize adolescents through health education about ABC strategies and safe male circumcision importance in an effort to combat HIV new infections.